The Determinants Of Industrialization: Empirical Evidence For Africa - Samouel, Beji; Aram, Belhadj (European Scientific Journal, ESJ, 2016)
In this paper, we run dynamic panel model describing the relationship between industrialization and different socio-economic, financial and institutional determinants for 35 African countries over the period 1970- 2012. We conduct also sub-regional and sub-period analysis in order to check the robustness of the results. Our main results are the following: (i) As generally found in the literature, Human capital, Labor Market conditions, Real Effective Exchange Rate and GDP per capita are clear determinants of industrialization in Africa; (ii) The determinants of industrialization vary between regions in the continent and evolve over time; (iii) policy interdependencies are significant and positive for industrialization in Africa.